2014
DOI: 10.5051/jpis.2014.44.6.288
|View full text |Cite
|
Sign up to set email alerts
|

Statistical methods used in articles published by the Journal of Periodontal and Implant Science

Abstract: PurposeThe purposes of this study were to assess the trend of use of statistical methods including parametric and nonparametric methods and to evaluate the use of complex statistical methodology in recent periodontal studies.MethodsThis study analyzed 123 articles published in the Journal of Periodontal & Implant Science (JPIS) between 2010 and 2014. Frequencies and percentages were calculated according to the number of statistical methods used, the type of statistical method applied, and the type of statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Before entering the preprocessing stage, the data obtained using the scraping method will be analyzed in advance about the number of reviews and ratings available on e-commerce 1, e-commerce 2, and e-commerce 3 e-commerce [21]. Descriptive analysis results will be visualized to know three e-commerce sites [22], [23].…”
Section: Descriptive Analysismentioning
confidence: 99%
“…Before entering the preprocessing stage, the data obtained using the scraping method will be analyzed in advance about the number of reviews and ratings available on e-commerce 1, e-commerce 2, and e-commerce 3 e-commerce [21]. Descriptive analysis results will be visualized to know three e-commerce sites [22], [23].…”
Section: Descriptive Analysismentioning
confidence: 99%
“…On the other hand, the use of complex and inefficient statistical methods solely for the purpose of superficial improvement of the study can be considered as an immoral approach. [1][2][3][4][5] Medical journals with a wide coverage of various topics in the field of medicine and public health have many enthusiasts around the world. In Iran, the Archives of Iranian Medicine (AIM) is a valuable journal and a reputable clinical resource that has been working since 1998 and has been publishing articles monthly since 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical review of journal articles is usually done over a period of 5 or 10 years. 3,4 At the time of conducting this study (June 2020), AIM's 2020 issues were not yet complete, so this year was not included in our study. Therefore, the period from 2015 to 2019 was selected as our study period.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they showed how articles that are published in certain dental journals applied and reported statistical methods differently from articles in visible medical journals (New England Journal of Medicine and Lancet) [11]. However, Choi et al [12] have identified a recent, but growing, trend towards the application of statistical, especially non-parametric, methods in periodontal research. There have also been also reviews of dental literature that have estimated the prevalence of misused statistics or statistical errors [13] or evaluated the quality of statistical reporting [10,14].…”
Section: Introductionmentioning
confidence: 99%